Alkane Biosynthesis Genes in Cyanobacteria and Their Transcriptional Organization - Klähn, Stephan; Baumgartner, Desirée; Pfreundt, Ulrike; Voigt, Karsten; Schön, Verena; Steglich, Claudia; Hess, Wolfgang R. (Frontiers in Bioengineering and Biotechnology, 2014)
In cyanobacteria, alkanes are synthesized from a fatty acyl-ACP by two enzymes, acyl-acyl carrier protein reductase (AAR) and aldehyde deformylating oxygenase (ADO). Despite the great interest in the exploitation for biofuel production, nothing is known about the transcriptional organization of their genes or the physiological function of alkane synthesis. The comparison of 115 microarray datasets indicates the relatively constitutive expression of aar and ado genes. The analysis of 181 available genomes showed that in 90% of the genomes both genes are present, likely indicating their physiological relevance. In 61% of them they cluster together with genes encoding acetyl-CoA carboxyl transferase and a short chain dehydrogenase, strengthening the link to fatty acid metabolism and in 76% of the genomes they are located in tandem, suggesting constraints on the gene arrangement. However, contrary to the expectations for an operon, we found in Synechocystis sp. PCC 6803 specific promoters for the two genes, sll0208 (ado) and sll0209 (aar), that give rise to monocistronic transcripts. Moreover, the upstream located ado gene is driven by a proximal as well as a second, distal, promoter, from which a third transcript, the ~160 nt sRNA SyR9 is transcribed. Thus, the transcriptional organization of the alkane biosynthesis genes in Synechocystis sp. PCC 6803 is of substantial complexity. We verified all three promoters to function independently from each other and show a similar promoter arrangement also in the more distant Nodularia spumigena, Trichodesmium erythraeum, Anabaena sp. PCC 7120, Prochlorococcus MIT9313 and MED4. The presence of separate regulatory elements and the dominance of monocistronic mRNAs suggest the possible autonomous regulation of ado and aar. The complex transcriptional organization of the alkane synthesis gene cluster has possible metabolic implications and should be considered when manipulating the expression of these genes in cyanobacteria.